PENGARUH KEGIATAN MEMBUAT KARYA SENI RUPA DALAM BENTUK DUA DIMENSI TERHADAP KEMAMPUAN MOTORIK HALUS ANAK USIA 5-6 TAHUN DI RA MAUI’ZAH HASANAH KECAMATAN TAMPAN KOTA PEKANBARU - Natasya Novriani; Daviq Chairilsyah; Hukmi Hukmi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: based on the resut of observation on fine motoric ability of young learners has not developed optimally. So it is necessary to implement the activity make artwork in two dimensional form. The objective of the research is to find out the effect of the activity of making atwork in two dimensional form on fine motoric ability on children age 5-6 years at RA Maui’zah Hasanah Tampan subdistrict Pekanbaru. The sample used in this research are 15 young learners. The data collection technique used are observation and documentation. The data analysis technique used t-test and SPSS 20 program. The hyphothesis of the research is there an effect of the ctivity of making artwork in two dimensional form on fine motoric ability on chidren age 5-6 years at RA Maui’zah Hasanah Tampan subdistict Pekanbaru. It can be seen by the data nalysis result thitung= 34.682 and sig (2 tailed)= 0.000, because sig (2-tailed) = 0.000 < 0.05, it can be concluded that there is a significant effect on fine motoric ability before and after conducted an experiment by applying activity of making artwork in two dimensional form in the lesson. It means that Ho is rejected and ha is accepted and there is a significant effect of activity of making artwork in two dimensional form on fine motoric ability. The effecct of the activity of making artwork in two dimensional form on fine motoric ability on children age 5-6 years at RA Maui’zah Hasanah Tampan Subdistrict Pekanbaru are 49%.Key words: fine motoric ability, the activity of making artwork in two dimensional form